2020
DOI: 10.4155/bio-2020-0263
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Adverse Analytical Findings in Individual and Team Sports

Abstract: The aim of this investigation was to describe the outcomes of the adverse analytical findings in different Olympic sports. The data included were gathered from the World Anti-Doping Agency Anti-doping Rule Violations Reports (2013–2017). Weightlifting (78.1 ± 9.4%) wrestling (73.2 ± 18.5%) and volleyball (68.3 ± 18.7%) were the sports with the highest proportion of cases that ended in an antidoping sanction. Gymnastics (45.1 ± 10.1%), triathlon (32.6 ± 11.9%) and shooting (29.9 ± 14.1%) were the sports with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous investigations on PED use have determined significant differences in doping prevalence when comparing sport disciplines and categories [ 6 , 14 , 15 ]. Apparently, doping prevalence among individual and power sports athletes is higher than in team or motor skill sports, but they are also more likely to be tested [ 13 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations on PED use have determined significant differences in doping prevalence when comparing sport disciplines and categories [ 6 , 14 , 15 ]. Apparently, doping prevalence among individual and power sports athletes is higher than in team or motor skill sports, but they are also more likely to be tested [ 13 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, prevalence research using randomized questionnaires revealed that up to 39% of elite athletes consumed prohibited substances intentionally in the last year [ 4 , 5 ]. Therefore, some investigations have questioned the efficiency of the system in the detection process and in the institutional strategy associated with the anti-doping fight [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consideration of the acknowledged existence of a majority of athletes that strictly disapproves doping, 8,9 various different research topics were compiled and prioritized in a concerted effort including 82 anti‐doping stakeholders, 10 aiming at respecting the needs, requests, and expectations of all parties. In a variety of studies, the essential and indispensable role of conventional anti‐doping tests in combination with doping control sample long‐term storage and re‐testing programs was summarized, 11–14 highlighting the importance of harmonizing especially global anti‐doping testing frequencies, an aspect that has not been fully accomplished today 15 and which experienced a severe setback particularly during the most critical months of the COVID‐19 pandemic 16,17 . The pandemic, however, fueled efforts in expanding testing options, particularly by means of modern options including remote testing strategies utilizing complementary matrices such as dried blood spots (DBS), 18,19 which support on the one hand anti‐doping organizations' efforts in addressing their commitments in testing, deterrence, and follow‐up investigations in case of atypical (ATF) as well as adverse analytical findings (AAFs), and on the other hand, the clean athletes in maintaining a continuous and frequent series of anti‐doping tests, 20 corroborating (while not unequivocally proving 21 ) their compliance to anti‐doping rules.…”
Section: Introductionmentioning
confidence: 99%